1983
DOI: 10.1164/arrd.1983.127.5.563
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Disposition of Tobramycin1,2

Abstract: Each antibiotic has a characteristic penetration into respiratory secretions, influenced by serum concentration, protein binding, transport systems, and the presence of infection. Whereas previous studies have used only bronchial secretions and blood, in the present study, blood, bronchial secretions, and bronchoalveolar lavage (BAL) fluid were analyzed for tobramycin levels. In 10 studies in 9 patients, serum levels were significantly related to BAL fluid levels (r = 0.8, p less than 0.01) when both were expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…However, signifi cant differences of antibiotic concentrations have been described between bronchial secretions and acini in the lower respiratory tract. 48 • Correlating pharmacokinetic data to a histological site. For biopsy with consecutively tissue homogenization admixture of concentrations of blood, and intracellular and extracellular contents is unavoidable.…”
Section: Methodical Considerations For Determining Concentrations Of mentioning
confidence: 99%
“…However, signifi cant differences of antibiotic concentrations have been described between bronchial secretions and acini in the lower respiratory tract. 48 • Correlating pharmacokinetic data to a histological site. For biopsy with consecutively tissue homogenization admixture of concentrations of blood, and intracellular and extracellular contents is unavoidable.…”
Section: Methodical Considerations For Determining Concentrations Of mentioning
confidence: 99%
“…The parenteral administration of aminoglycosides in humans, however, is associated with relatively low lung concentrations of these antibiotics, and high peak serum concentrations (C max ) are needed to obtain microbiologically active concentrations in the alveoli, in the pulmonary interstitium, and intracellularly within macrophages, the most common sites of M. tuberculosis infection. In the few published clinical studies specifically evaluating alveolar lining fluid concentrations of aminoglycosides after systemic administration, alveolar concentrations ranged from 32% to 50% of the peak systemic concentration (9)(10)(11). Furthermore, preclinical studies of capreomycin pharmacokinetics in mice have shown that parenteral doses penetrate poorly into the lung (12).…”
mentioning
confidence: 99%
“…Concentrations in ELF were well correlated with concentrations in plasma, with mean ratios of 10.8 and 6.05% in groups A and B, respectively. Previous studies have evaluated the penetration of antibiotics into the ELF with very different results: the ratios of concentrations in ELF to concentrations in serum were 17% for roxithromycin (3), 53% for ampicillin, 51% for sulbactam (16), and 50% for tobramycin (2). These variations could have resulted from two main differences in these studies.…”
Section: Discussionmentioning
confidence: 94%
“…(i) The modes of administration were different, since tobramycin and ampicillin-sulbactam were administered intravenously (over 30 min for the P-lactams), whereas cefpodoxime and roxithromycin were administered orally. (ii) The sampling times could be considered the times of maximum concentrations in plasma for all of the drugs except tobramycin, for which the sampling times ranged from 1 to 10 h (similarly, the doses ranged (2,8). We notice, however, that all the pathologies, even the variable ones, might be responsible for an increase in alveolar capillary permeability due to edema or interstitial inflammation.…”
Section: Discussionmentioning
confidence: 99%